PROVISIONS FOR WRITING NUMBERS IN NOTARY DEED - Sitti Putri Utami; Nurfaidah Said; Hasbir Paserangi; Muhammad Ilham Arisaputra (Surakarta Law and Society Journal, 2020)
Purpose this research is to discuss about provisions for writing numbers in a notary deed. The result indicated that is in principle, the deed contains the statements and wishes of the parties before the Notary which are set forth in writing. Therefore, according to the author, the contents of a deed are basically writings which are the wishes of the parties. Decree of the Minister of Education and Culture of the Republic of Indonesia Number 054a /U/1987 stipulates that numbers do not need to be written with numbers and letters at the same time in the text, except in official documents such as deeds and receipts. Because deeds made by notaries are official documents which are state archives, the writing of numbers in the notary deeds follows the ministerial decree. Based on the provisions above, if there is a difference between the writing of numbers and the writing of letters (text or spelled out) in a deed, then what is followed is the one written completely in letters. Likewise, if the deed is used as evidence, the judge must follow what is written in full in letters. Keywords: Notary, deed, numbers.